2013
DOI: 10.1002/adhm.201200330
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self‐Assembling Mixed Protein Micelles with Temperature‐Modulated Avidities

Abstract: Elastin-like polypeptides (ELPs) are polypentapeptides that undergo hydrophobic collapse and aggregation above a specific transition temperature, Tt. ELP diblocks sharing a common “core” block (I60) but varying “outer” blocks (A80, P40) were designed, where Tt,I < Tt,A < Tt,P. The formation of ~55 nm diameter mixed micelles from these ELP diblocks was verified using dynamic light scattering (DLS), multiangle light scattering (MALS) and fluorescence resonance energy transfer (FRET). To confer affinity to the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…These mimics can then be used alone, or in conjunction with carrier materials, to modify fibrin structure. We subsequently created a variety of knob mimic constructs including knob A -protein constructs, PEGylated knobs A and B and knob A modified elastin-like peptide (ELP) micelles and characterized their effect on fibrin properties such as polymerization, degradation and mechanical properties and network structure [31, 43, 151153]. Knob A -protein constructs designed to display the tetrapeptide sequences GPRP, GPRV, GHRP or GSPE (non-binding control) at the N-termini of a protein fragment, specifically the cell binding 9th and 10th type III repeats of fibronectin, were found to stably bind fibrinogen via specific knob:hole interactions and were retained within fibrin matrices for 24 hours, therefore showing promise as a potential method for drug release from fibrin matrices [152].…”
Section: Modulation Of Fibrin Propertiesmentioning
confidence: 99%
“…These mimics can then be used alone, or in conjunction with carrier materials, to modify fibrin structure. We subsequently created a variety of knob mimic constructs including knob A -protein constructs, PEGylated knobs A and B and knob A modified elastin-like peptide (ELP) micelles and characterized their effect on fibrin properties such as polymerization, degradation and mechanical properties and network structure [31, 43, 151153]. Knob A -protein constructs designed to display the tetrapeptide sequences GPRP, GPRV, GHRP or GSPE (non-binding control) at the N-termini of a protein fragment, specifically the cell binding 9th and 10th type III repeats of fibronectin, were found to stably bind fibrinogen via specific knob:hole interactions and were retained within fibrin matrices for 24 hours, therefore showing promise as a potential method for drug release from fibrin matrices [152].…”
Section: Modulation Of Fibrin Propertiesmentioning
confidence: 99%
“…28 This is supported by a recent report, which confirmed the in vitro coassembly of two ELP diblock copolymers into mixed micelles, whereby one ELP-bound fibrinogen and a second ELP provided temperature-dependent reversal of binding. 47 To develop the first in vivo evidence that multiple ELP diblock copolymers can work together to improve the delivery of a small molecule, this manuscript describes two ELP diblock copolymer fusions (FSI and ISR) that assemble at physiological temperature into bifunctional nanoparticles (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Soon et al [60] demonstrated a gradual, controlled selfassembly of ELP diblocks to micelles to micron-sized aggregates. Two types of diblocks were used in this study: I 60 40 .…”
Section: Self-assembly Of Elps Into Hierarchical Structuresmentioning
confidence: 99%
“…Two types of diblocks were used in this study: I 60 40 . The A 80 block was decorated with a fibronectin binding group.…”
Section: Self-assembly Of Elps Into Hierarchical Structuresmentioning
confidence: 99%